The Effect of Feedback at Different Times by Using Multimedia in Learning the Performance of Some Basic Skills in Handball For Students - Hamida Obaid Abdulamir; Nisreen Hassan Naji; Naseer Ahmad Kamil (Institute of Medico-legal Publications Pvt Ltd, 2021)
The handball game has taken to keep pace with the development and progress in the world, where manychanges have occurred in the methods of learning and training in various aspects, including in particularchanges in the methods of playing teams in terms of applying defensive and offensive plans in order tosurprise the competitor, and the use of feedback in the process of learning and developing basic skills Byvarying the time it is given in order to make the learner have the ability to absorb the skill and the processof choosing the appropriate motor program to solve the motor duty in the best way and according to therequirements of the situation facing him. Conclusions: The use of times (10, 20, 30 seconds) to providefeedback of all kinds has an impact. Positively in learning basic handball skills and for the three groups,the use of multimedia (visual display device “Data show”, video cameras, color papers for the movementsequence of skills, display of the live model) has a great role in developing basic skills of handball throughincreasing motivation In competition between players, a time of (10, 30) seconds in providing feedback ismore influential in learning basic handball skills.